Coordination of transposon expression with DNA replication in the targeting of telomeric retrotransposons in Drosophila. - Zhang, L.; Beaucher, M.; Cheng, Y.; Rong, Y.S. (The EMBO Journal, 2014)
In Drosophila, a group of retrotransposons is mobilized exclusively to telomeres in a sequence-independent manner. How they target chromosome ends is not understood. Here, we focused on the telomeric element HeT-A and characterized the cell cycle expression and cytological distribution of its protein and RNA products. We determined the timing of telomere replication by creating a single lacO-marked telomere and provide evidence suggesting that transposon expression and recruitment to telomeres is linked to telomere replication. The HeT-A-encoded ORF1p protein is expressed predominantly in S phase, particularly in early S phase. Orf1p binds HeT-A transcripts and forms spherical structures at telomeres undergoing DNA replication. HeT-A sphere formation requires Verrocchio, a putative homolog of the conserved Stn1 telomeric protein. Our results suggest that coupling of telomere elongation and telomere replication is a universal feature, and raise the possibility that transposon recruitment to Drosophila telomeres is mechanistically related to telomerase recruitment in other organisms. Our study also supports a co-adaptive relationship between the Drosophila host and HeT-A mobile elements.